Combination of gefitinib and methotrexate to treat tubal ectopic pregnancy (GEM3): a multicentre, randomised, double-blind, placebo-controlled trial. Issue 10377 (25th February 2023) - Horne, Andrew W; Tong, Stephen; Moakes, Catherine A; Middleton, Lee J; Duncan, W Colin; Mol, Ben W; Whitaker, Lucy H R; Jurkovic, Davor; Coomarasamy, Arri; Nunes, Natalie; Holland, Tom; Clarke, Fiona; et al.
Summary: Background: Tubal ectopic pregnancies can cause substantial morbidity or even death. Current treatment is with methotrexate or surgery. Methotrexate treatment fails in approximately 30% of women who subsequently require rescue surgery. Gefitinib, an epidermal growth factor receptor inhibitor, might improve the effects of methotrexate. We assessed the efficacy of oral gefitinib with methotrexate, versus methotrexate alone, to treat tubal ectopic pregnancy. Methods: We performed a multicentre, randomised, double-blind, placebo-controlled trial across 50 UK hospitals. Participants diagnosed with tubal ectopic pregnancy were administered a single dose of intramuscular methotrexate (50 mg/m 2 ) and randomised (1:1 ratio) to 7 days of additional oral gefitinib (250 mg daily) or placebo. The primary outcome, analysed by intention to treat, was surgical intervention to resolve the ectopic pregnancy. Secondary outcomes included time to resolution of ectopic pregnancy and serious adverse events. This trial is registered at the ISRCTN registry, ISCRTN 67795930. Findings: Between Nov 2, 2016, and Oct 6, 2021, 328 participants were allocated to methotrexate and gefitinib (n=165) or methotrexate and placebo (n=163). Three participants in the placebo group withdrew. Surgical intervention occurred in 50 (30%) of 165 participants in the gefitinib group and in 47 (29%) of 160 participants in the placebo group (adjusted risk ratio 1·15, 95% CI 0·85 to 1·58; adjusted risk difference –0·01, 95% CI –0·10 to 0·09; p=0·37). Without surgical intervention, median time to resolution was 28·0 days in the gefitinib group and 28·0 days in the placebo group (subdistribution hazard ratio 1·03, 95% CI 0·75 to 1·40). Serious adverse events occurred in five (3%) of 165 participants in the gefitinib group and in six (4%) of 162 participants in the placebo group. Diarrhoea and rash were more common in the gefitinib group. Interpretation: In women with a tubal ectopic pregnancy, adding oral gefitinib to parenteral methotrexate does not offer clinical benefit over methotrexate and increases minor adverse reactions. Funding: National Institute of Health Research.